WUJUD KEPEDULIAN MELAWAN COVID-19 MELALUI KEGIATAN PEMBAGIAN NEW NORMAL KIT KEPADA PEDAGANG PASAR TIDUNG KOTA MAKASSAR: A Form of Concern Against Covid-19 Through The Activities of the New Normal Kit to Market Traders Tidung City of Makassar - A. Tenriugi Daeng Pine; Suhartini; Dzul Asfi; Andi Hasisah; Thahir, Zakiah (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2022)
Market is one of the spread of Covid-19 was the cluster , so that the market as requiring specialattention to order to prevent the spread of the virus corona .As an effort to prevent the spreading ofCovid-19 in market environment , done devotion the community whose aim is to order to prevent thespread via the division of new normal kit to the traders Tidung market Bonto Makkio the city ofMakassar. The devotion is preventive measures 19 covid transmission of the pandemic the Heart' ' seenas a community of economics .If the heart is disabled and move , economy and will be paralysed .It is thedevotion to the high interest traders team devotion and accept with very enthusiastic new normal kitdistributed. Enthusiastic people show that they need protection of virus Covid-19 that attacks of therespiratory tract and the highly lethal .Great expectations of the team pkm to the activities of this is itmay be that the people who receive new normal kit can provide education to the people conveying towear mask when being out of the house and in public places , washing your hands after contact directlywith others , and always keep at a distance